فقه الراشدين من خلال موطأ الإمام مالك - بعيطيش زكرياء عبدالعزيز; تناح بولرباح; د/بوفاتح الطيب (جامعة عمار ثليجي الاغواط, 2023)
124 إن مشروع البحث العلمي المقدم أمامكم ، ينبني على شقين أساسيين ، شق نظري عالج الأبعاد الاصطلاحية ، وملامح الفقه في عصر الخلفاء الراشدين وشق تطبيقي عالج المسائل الفقهية للخلفاء الراشدين الواردة في العبادات من خلال موطأ الإمام مالك ، والذي اعتمد فيه بشكل كبير على الآثار الواردة عن الخلفاء الراشدين ، وهذا ما سمي بالموقوفات التي وضّحناها و بيّننا حجيتها ، وهذا إن دلّ على شيء فإنه يدل على أن أفعال الخلفاء الراشدين وأقوالهم ، تعتبر مصدراً قويما ، يركن إليه في الفقه ، لأن جملة فتاويهم توافق صريح القرآن الكريم و السنة النبوية بما كان فهمهم السليم ، واستنباطهم المؤسّس على معاصرتهم للوحي الكريم المشرِّع لأفعال المكلفين. وجملة ما عالجناه في الجانب التطبيقي من بحثنا ، هي مسائل كثيرة قد اجتهد الخلفاء الراشدون فيها ، مثل قتال مانعي الزكاة ، و جمع المسلمين على قارئ واحد في التراويح ، أيضا بعض المسائل الفرعية التي تصدّى الخلفاء لتبيينها ، أهمها الصلاة ومواقيتها ، العمل فيها من قصر السفر و القراءة فيها وغيرها وكذا الزكاة و تبيين مقاديرها ، التشديد عل وجوبها ، والتيسير على المسلمين فيها ، بعض المسائل مثل الزكاة في الدين، و أيضاً الحج والذي تمثل تفسير مبهم مسائله ، تفصيل بعض الخلاف الذي وقع فيه مثل مسائل الإقران و الإفراد و التمتع . Summary : The present project includes two main sections ,a theoritical and a practical section. The theoritical part includes the definition of of the key terms .In addition to the biography of the four rightly guided caliphs _Abu Bakker ,Omar ,Othman and Ali -may Allah bless all of them-. Furthermore, we gave a description of the overall condition of the Fiqh law and it's impact on the political stability in the era of the rightly guided caliphs (may Allah bless them)as well as the Imam Malik era . We concluded that the political stability had an effect on the progress of the islamic Shariaah law. The Muatta of imam malik adopt several speeches and acts of the rightly guided caliphs named the suspended hadiths which we explained their meaning and how much we can take them as an argument.This indicates that the acts of the Four rightly guided caliphs are considered as a main source that we highly depend on in the islamic legislation. Due to their resemblance and extendance of their Fatwa's with the Holy Quran and the Sunnah of the prophet -peace be upon him-. Furthermore, their clear understanding of the legal rules and judgement from the general premises because they lived in the era if the devining legeslation . the practical part processed several issues such as : the legal necessity of the Zakah , collecting people behind one Imam in the prayer of Ramadan ....etc Besides,we have shown some of the sub-issues for instance: times of obligatory prayers , Zakah upon debts as well as some of the controversial issues in the Pilgrimage.